1993
DOI: 10.1063/1.165982
|View full text |Cite
|
Sign up to set email alerts
|

Solution multistability in first-order nonlinear differential delay equations

Abstract: The dependence of solution behavior to perturbations of the initial function (IF) in a class of nonlinear differential delay equations (DDEs) is investigated. The structure of basins of attraction of multistable limit cycles is investigated. These basins can possess complex structure at all scales measurable numerically although this is not necessarily the case. Sensitive dependence of the asymptotic solution to perturbations in the initial function is also observed experimentally using a task specific electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 24 publications
1
45
0
1
Order By: Relevance
“…The existence of such time delays is absolutely essential to ensure that the solution is always uniquely determined (Milton et al 1989;). Multistability and other complex dynamics readily arise in these examples (Losson et al 1993;Foss et al 1997). Although the effects of noise have received comparatively little attention Eurich & Milton 1996), it is obvious that switching between coexisting attractors will add further complexity.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of such time delays is absolutely essential to ensure that the solution is always uniquely determined (Milton et al 1989;). Multistability and other complex dynamics readily arise in these examples (Losson et al 1993;Foss et al 1997). Although the effects of noise have received comparatively little attention Eurich & Milton 1996), it is obvious that switching between coexisting attractors will add further complexity.…”
Section: Discussionmentioning
confidence: 99%
“…It is even possible to construct the solution using a compass and a ruler [3]! Moreover, experimental paradigms using piecewise constant types of feedback can be developed and used to directly compare prediction with observation [51,52,58,72,64]. (20) observed as a function of C and τ (see [28] for details).…”
Section: Stabilizing the Upright Positionmentioning
confidence: 99%
“…5,35,36 The dependence of the solutions on the initial function in the MG model and in other first order DDEs was investigated by Losson et al 5 They showed, by means of numerical and experimental methods, that the basins of attraction of piecewise constant feedback DDE can possess a complex structure at all scales measurable numerically. Specifically in relation with the MG model, Losson et al focus on a family of sinusoidal IFs, which parameter values give rise to limit cycles either with strictly positive or negative values of the variable.…”
Section: The Mg Modelmentioning
confidence: 99%
“…30 Several groups have proposed experimental implementations of the MG model via electronic circuits. 5,19,29,[31][32][33] An electronic implementation based on an analog delay line was considered in Refs. 19,28, and 31 to address the problem of synchronization and control of high dimensional chaos.…”
Section: The Mg Modelmentioning
confidence: 99%
See 1 more Smart Citation